The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/10400435.2014.926468
|View full text |Cite
|
Sign up to set email alerts
|

A Detachable Electronic Device for Use With a Long White Cane to Assist With Mobility

Abstract: Vision-impaired individuals often use a long white cane to assist them with gathering information about their surroundings. However, these aids are generally not used to detect obstacles above knee height. The purpose of this study is to determine whether a low-cost, custom-built electronic device clipped onto a traditional cane can provide adequate vibratory warning to the user of obstacles above knee height. Sixteen normally sighted blindfolded individuals participated in two mobility courses which they navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…Therefore, the results for walking speed, which also agree with observations made by O'Brien et al [42], seem to confirm hypothesis 1, namely that blindfolding non-visually impaired participants is an inaccurate substitute for blind participants in white cane experiments. Results obtained with non-visually impaired users will not necessarily generalize to visually impaired users.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the results for walking speed, which also agree with observations made by O'Brien et al [42], seem to confirm hypothesis 1, namely that blindfolding non-visually impaired participants is an inaccurate substitute for blind participants in white cane experiments. Results obtained with non-visually impaired users will not necessarily generalize to visually impaired users.…”
Section: Discussionsupporting
confidence: 90%
“…Based on these results, which also agree with observations by O'Brien et al [42], we can only partially accept hypothesis 2, namely that electronic canes with additional obstacle cues lead to improved performance over traditional passive white canes, as the only observed benefit were the ability to detect hanging obstacles which cannot be detected by the white canes. In terms of ground obstacles, hypothesis 2 is rejected.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Most of the tested devices have been designed to be used as a secondary device, complementing a traditional long cane as an attachment to the long cane (Gallo et al, 2010; S. Kim & Cho, 2013; O’Brien, Mohtar, Diment, & Reynolds, 2014; Pyun, Kim, Wespe, Schneller, & Gassert, 2013; Tahat, 2009; Wang & Kuchenbecher, 2012). The majority of these studies reported a moderate improvement in object detection rate, largely as a result of detecting above-waist-level overhanging obstacles, which the traditional long cane is inherently unable to detect.…”
Section: Introductionmentioning
confidence: 99%
“…Esta situación generará una carga social, económica y cultural de alcance universal, con énfasis en los países de ingresos medianos y bajos [1]. Aunque existen ayudas para mejorar la visión residual en personas con discapacidad visual leve a moderada, estas no sirven para personas con discapacidad visual severa a profunda (DVS, DVP) o con ceguera, las cuales necesitan desarrollar habilidades que sustituyan la visión [4]. Para ellas el logro de la independencia en actividades básicas e instrumentales de la vida diaria es más difícil, teniendo en cuenta que puede coexistir otro tipo de discapacidades que limitan aún más este proceso.…”
Section: Introductionunclassified